INVESTIGATION OF BACTERIAL HOPANOID INPUTS TO SOILS FROM WESTERN CANADA - Shunthirasingham C.; Simpson M.J. (My University, 2006)
Hopanoids have been widely used as characteristic biomarkers to study inputs of bacterial biomass to sediments because they are preserved in the geologic record. A limited number of studies have been performed on hopanoid biomarkers in soils. The present study examined the distribution and potential preservation of hopanoids in soils that are developed under different climatic conditions and varying vegetative inputs. Solvent extraction and sequential chemical degradation methods were employed to extract both "free" and "bound" hopanoids, from three grassland soils, a grassland-forest transition soil, and a forest soil from Western Canada. Identification and quantification of hopanoids in the soil samples were carried out by gas chromatography-mass spectrometry. Methylbishomohopanol, bishomohopanol and bishomohopanoic acid were detected in all solvent extracts. The base hydrolysis and ruthenium tetroxide extracts contained only bishomohopanoic acid at a concentration range of 0.8-8.8 μg/gC and 2.2-28.3 μg/gC, respectively. The acid hydrolysis procedure did not release detectable amounts of hopanoids. The solvent extraction yielded the greatest amounts of "free" hopanoids in two of the grassland soils (Dark Brown and Black Chernozems) and in the forest soil (Gray Luvisol). In contrast, the chemical degradation methods resulted in higher amounts of "bound" hopanoids in the third grassland soil (Brown Chernozem) and the transition soil (Dark Gray Chernozem), indicating that more hopanoids exist in the "bound" form in these soils. Overall, the forest and the transition soils contained more hopanoids than the grassland soils. This is hypothesized to be due to the greater degradation of hopanoids in the grassland soils and or sorption to clay minerals, as compared to the forest and transition soils. © 2006 Elsevier Ltd. All rights reserved.